Image steganography method based on complementary image - Сулема, Євгенія Станіславівна; Широчин, Семен Станіславович (Ukrainian Information Security Research Journal, 2013)
Abstract. Digital images while either transferring via Internet or storing in common-used servers can easily get into open access. If these images are private, the task of their simple and effective protection becomes topical for a user. Furthermore, time of image processing while protecting is important for an ordinary user. The existing cryptographic methods are not oriented to an ordinary user who needs a simple and fast method for graphical data security while transferring them via network in real time. This paper proposes the steganographic method for digital images protection based on storage of a complementary image instead of the stego-image as well as on using a randomized Latin square as a key. The developed method provides better time performance in encoding and decoding of user data than similar cryptographic methods. It is achieved by using parallel computing. The proposed method can be used in real-time for the protection of private images of a user before their transfer via network. Hidden images can be saved in either png or lossless jpeg formats.